Contamination Status of Surface Water from the Balu River for Irrigation Usage in Bangladesh (Journal of Environmental Science and Natural Resources, 2021)
An attempt was made to evaluate the contamination status of surface water collected from the Balu river for irrigation. Twenty samples were collected to analyze pH, EC, TDS and ions. Samples were slightly alkaline in nature. Water samples were from low to medium salinity and low alkalinity hazards (C1S1-C2S1). As per TDS values, samples were classified as freshwater. Considering SAR and SSP values, samples were excellent and good to permissible classes, respectively. Most of the water samples were free from RSC and all the samples were under moderately hard. The status of Cr and Mn ions in samples surpassed FAO guideline values indicating contaminants for long-term irrigation. The levels of other metal ions in samples were within acceptable levels and did not pose a threat to irrigated soil. This finding revealed that Cr and Mn ions were considered as contaminants in river water for irrigation posing harmful impact on soils and crops.Environ. Sci. & Natural Resources, 12(1&2): 57-65, 2019